Determination of The Biodiesel Production Process from Palm Fatty Acid Distillate and Methanol - Supranto Supranto (Seminar Nasional Teknik Kimia Kejuangan, 2015)
In the 21st century, Indonesia was predicted will become one of the petroleum net-importer countries. Alternative of energy resources, including biodiesel would have to be developed as energy sources for transportation and electric generation. Oil Palm and its chemicals derivatives have been identified as the most potential raw material for biodiesel production. A study of the biodiesel production process from palm fatty acid distillate (PFAD) and methanol have been done. Laboratory experimental work has been carried out. The chemical process condition of the biodiesel production from PFAD and methanol has been experimentally identified. The chemical process condition of 65 oC, 90 minute processing and sulfuric acid catalyst amount of 1.2 % can be used as the chemical process condition for the design of biodiesel production process.